Total productive maintenance, total quality management and operational performance: An empirical study of Indian pharmaceutical industry. Issue 4 (10th October 2016) - Modgil, Sachin; Sharma, Sanjay
Abstract : Purpose: The purpose of this paper is to investigate the impact of total productive maintenance (TPM) and total quality management (TQM) practices on operational performance and their inter-relationship. Design/methodology/approach: The present study includes three main constructs, namely, TPM, TQM and operational performance of pharmaceutical industry. Under TPM, four constructs, namely, disciplined maintenance, information tracking, housekeeping and operator involvement has been considered with the help of literature. In TQM, four constructs, namely, quality data and reporting, product innovation, research and development (R&D) management and technology management has been considered. Out of 410 Indian pharmaceutical plants contacted for survey, 254 responses have been used in the study for analysis. The factor analysis, path model and structural equation modeling has been used to analyze the proposed framework. The results for alternate models has been studied, interpreted and reported. Finally the direct and indirect effect of TPM and TQM on operational performance has been tested and checked for proving and disproving the hypotheses. Findings: TPM practices have a significant impact on plant-level operational performance. When TPM and TQM practices are coming together to achieve operational performance, then TPM is having strong influence on operational performance. TQM is having significant support from TPM to achieve operational performance. TPM impact TQM and TQM in turn helps to achieve operational performance. TPM practices impact significantly R&D, product innovation and technology management, whereas quality data and reporting is the least contributor toward TQM. This may help industry to understand implications of implementation of TPM and TQM to achieve plant-level operational performance. TPM will help to reduce the cost of quality in terms of reduced scrap and less defective products. Practical implications: The present study provides the useful insights to practicing managers. In literature it has been mentioned that TQM helps in TPM implementation. In practice TPM plays a great role to achieve quality in processes and therefore in products. In turn quality products, with reduced work in process inventory, less defective products and reduced scrap helps to achieve the operational performance at plant level. TPM practices will help the organization to improve the pace of product innovation and improvement in productivity, which is critical to pharmaceutical industry. The continuous monitoring of TPM practices can help organizations to run day to day operations and maintenance requirement of each machine over a specified period of time. Originality/value: The present study diagnoses the inter-dimensional linkage between TPM, TQM and operational performance. The pharmaceutical industry is complex system of advance equipment's and processes. After human resources, the health of machines/equipment's describe the strength of an organization. The machines require the regular maintenance to produce the products with desired specifications. The specifications in medicines and very tight, which can be achieved only if machines/testing equipment's are updated and maintained regularly. The TPM practices will helps the plants to achieve the operational performance by having quality in processes.